Understanding the Potential of Using EdTech to Measure and Mitigate Learning Losses in Latin America and the Caribbean - Wyss, Natalie; Myers, Christina (EdTech Hub, 2022)
This document was produced in response to a request from the UNICEF Latin America and the Caribbean Regional Office (LACRO) submitted to the EdTech Hub Helpdesk in December 2021. The UNICEF team requested a resource that summarises what is known about the use of technology and other approaches to measure and mitigate learning losses related to Covid-19 impacts on education in the LAC region. This resource aims to support UNICEF country offices and partners in the LAC region to assess learning losses and inform school reopening and the development of hybrid education strategies. Our research found that there are limited EdTech approaches to measuring and mitigating learning losses, and fewer still that are specific to the LAC region. This piece outlines the following: What is understood about learning losses and how they can be quantified; What common guidance and evidence suggest are the most effective ways to mitigate Covid-19-specific learning losses; How established EdTech tools and non-tech-based approaches can be leveraged and applied to both processes. Keywords: learning losses; school reopening; personalised learning; assessment; remedial education An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Structured Pedagogy and EdTech - Adam, Taskeen; Chuang, Rachel; Haßler, Björn (EdTech Hub, 2021)
Keywords: _EdTechHub_Output; _MELA_seen; _coming soon; _cover:analysis:nopdf; dode_eth-src-eth; dode_eth-trf2-dode

Effective Use of EdTech for Remedial Learning Programmes: Considerations for Mongolia - Upadhyay, Arjun; Shoobridge, James; Moss Coflan, Caitlin (EdTech Hub, 2020)
This document was produced in response to a request from the World Bank Mongolia team to: 1. Outline the evidence of effective practices on remedial education generally. 2. Explore appropriate uses of EdTech to support remedial education. 3. Summarise the implications of these findings for Mongolia.
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _zenodo:submitted

18 large-scale EdTech initiatives on our radar in 2020 - Moss, Caitlin (EdTech Hub, 2020)
During the EdTech Hub’s inception phase so far, one question we hear a lot is: “What interesting or notable EdTech initiatives are you seeing?” Another question usually follows: “Which ones are reaching scale?” This week we have joined the global education community in London for the Education World Forum and BETT meetings. This is a […]
Keywords: F:Blog post; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH